Elite rhythmic gymnasts performance in relation to anthropometric, nutritional, biomechanical and technical aspects - Grande Rodriguez, I.; Figueroa Achapar, J.; Hontoria Galan, M.; Camara Hurtado, M.; Fernandez Ruiz, V.; Bautista Reyes, A. (Archivos de medicina del deporte, 2008)
Most of studies about rhythmic gymnastics have been focused on punctual measurements or evaluations as biological and biomechanical variables (Dyhre-Poulsen, 1987; Kulka, 1994), as well as the complex execution of movements made by gymnasts or the effect of high intensity training program at growing period (Georgopoulos, et al., 2001). In this work we propose an integrated longitudinal and applied study, of elite female rhythmic gymnasts, combining biological, biomechanical and nutritional evaluations with the judge`s measurements about gymnast`s executions. This is a longitudinal study carried out during the Olympic Games preparation program. Different measures had been taken along the training period to analyze the evolution and modifi cation of the different parameters as a result of high level training. Biomechanical parameters evaluated were principal explosive force test variables (Height (cm) and Power (W/Kg)). Biological evaluation included all the anthropometric parameters. Nutritional status of gymnasts had been evaluated by body mass index (BMI), food and calories intake, correlated with biological markers. Technical evaluation was based on judges punctuation related to difficulty degree and performance. The knowledge obtained will help to select which are the variables with more infl uence on the real performance in order to optimize the training and control process to improve gymnast competition level.